Pituitary-Thyroid System in Rats of Different Ages Under Desynchronosis, Whole-Body Cryostimulation, and Cord Blood Injection - Lomako, Victoria; Shylo , Oleksandr; Samokhina, Lyubov; Lutsenko, Dmytro (Problems of Cryobiology and Cryomedicine, 2022)
The state of the pituitary-thyroid system central and peripheral links (according to the levels of thyroid stimulating hormone (TSH) and thyroid hormones T4 and T3 in blood serum) were studied in 6- and 18-month-old rats under initiated circadian desynchronosis (CD) by the light regime inverting. The CD was simulated against the background of separate and combined eff ect of both the whole body cryostimulation (–120°C) (WBC) and injections of the nucleated cells (NCs) of human cord blood, applied preventively (for a day and week, respectively). In 6-month-old rats, the TSH level decreased under the CD and its initiation after separate NCs administration and combined with WBC (by 3.4, 3.9 and 6.3 times, respectively) and remained unchanged under CD against the WBC. In 18-month-old rats the TSH level was reduced only at CD by 1.8 times. The T4 level in rats of both age groups did not change under the CD as well as during its development against the background of a combined effect of WBC and NCs administration in 6-month-old animals and against the NCs injection in 18 months-old rats. The T4 level in rats of both age groups decreased at the background of separate effect of the WBC (by 1.6 and 1.4 times, respectively). In 18-month-old animals, the T4 increased under the CD development after a combined effect of WBC and NCs injection by 1.3 times. No changes in the T3 level were found. Probl Cryobiol Cryomed 2022; 32(3):196–205